Low level activity thresholds for changes in NMR biomarkers and genes in high risk subjects for Type 2 Diabetes - Herzig, Karl-Heinz; Leppäluoto, Juhani; Jokelainen, Jari; Meugnier, Emmanuelle; Pesenti, Sandra; Selänne, Harri; Mäkelä, Kari A.; Ahola, Riikka; Jämsä, Timo; Vidal, Hubert; Keinänen-Kiukaanniemi, Sirkka (Scientific reports, 2017)
Our objectives were to determine if there are quantitative associations between amounts and intensities of physical activities (PA) on NMR biomarkers and changes in skeletal muscle gene expressions in subjects with high risk for type 2 diabetes (T2D) performing a 3-month PA intervention. We found that PA was associated with beneficial biomarker changes in a factor containing several VLDL and HDL subclasses and lipids in principal component analysis (P = <0.01). Division of PA into quartiles demonstrated significant changes in NMR biomarkers in the 2nd - 4th quartiles compared to the 1st quartile representing PA of less than 2850 daily steps (P = 0.0036). Mediation analysis of PA-related reductions in lipoproteins showed that the effects of PA was 4–15 times greater than those of body weight or fat mass reductions. In a subset study in highly active subjects’ gene expressions of oxidative fiber markers, Apo D, and G0/G1 Switch Gene 2, controlling insulin signaling and glucose metabolism were significantly increased. Slow walking at speeds of 2–3 km/h exceeding 2895 steps/day attenuated several circulating lipoprotein lipids. The effects were mediated rather by PA than body weight or fat loss. Thus, lower thresholds for PA may exist for long term prevention of cardio-metabolic diseases in sedentary overweight subjects.